Pathogenic RBM20-Variants Are Associated With a Severe Disease Expression in Male Patients With Dilated Cardiomyopathy. (March 2019) - Hey, Thomas Morris; Rasmussen, Torsten B.; Madsen, Trine; Aagaard, Mads Malik; Harbo, Maria; Mølgaard, Henning; Møller, Jacob E.; Eiskjær, Hans; Mogensen, Jens
Abstract : Background: As pathogenic variants in the gene for RBM20 appear with a frequency of 6% among Danish patients with dilated cardiomyopathy (DCM), it was the aim to investigate the associated disease expression in affected families. Methods and Results: Clinical investigations were routinely performed in DCM index-patients and their relatives. In addition, ≥76 recognized and likely DCM-genes were investigated. DNA-sequence-variants within RBM20 were considered suitable for genetic testing when they fulfilled the criteria of (1) being pathogenic according to the American College of Medical Genetics and Genomics-classification, (2) appeared with an allele frequency of <1:10.000, and (3) segregated with DCM in ≥7 affected individuals. A total of 80 individuals from 15 families carried 5 different pathogenic RBM20 -variants considered suitable for genetic testing. The penetrance was 66% (53/80) and age-dependent. Males were both significantly younger and had lower ejection fraction at diagnosis than females (age, 29±11 versus 48±12 years; P <0.01; ejection fraction, 29±13% versus 38±9%; P <0.01). Furthermore, 11 of 31 affected males needed a cardiac transplant while none of 22 affected females required this treatment ( P <0.001). Thirty percent of RBM20 -carriers with DCM died suddenly or experienced severe ventricular arrhythmias although no adverse events were identified among healthy RBM20 -carriers with a normal cardiac investigation. The event-free survival of male RBM20 -carriers was significantly shorter compared with female carriers ( P <0.001). Conclusions: The disease expression associated with pathogenic RBM20 -variants was severe especially in males. The findings of the current study suggested that close clinical follow-up of RBM20 -carriers is important which may ensure early detection of disease development and thereby improve management. Abstract : Supplemental Digital Content is available in the text.